Verification and application of SuperMC3.3 to lead-bismuth-cooled fast reactor - Ding Hui (Nuclear Technology and Radiation Protection, 2019)
Lead-cooled fast reactors have multilayered designs and large internal temperature differences, which cause challenges in simulating reactor physics. SuperMC, a large-scale integrated software system for neutronics design, is inherently able to address complex geometries and multi-temperature problems. The purpose of this study is to verify the applicability of SuperMC to the lead-bismuth-cooled fast reactor RBEC-M. The multi-temperature cross-section generation function of SuperMC was employed and showed good performance. Based on the ENDF/B-VII.1 library, the effective multiplication factor keff obtained by SuperMC showed good agreement with those from previous works. The relationship of keff and 15N enrichment applied to the fuel material was also studied, with the results showing that in creased 15N could significantly improve keff. The axial power profile and kinetics parameters for the bench mark were then calculated and analyzed. This work thus verified the applicability of SuperMC for comprehensive neutronics simulations for lead-bismuth-cooled fast reactors.